PENGARUH MASA SIMPAN TERHADAP KUALITAS FISIK DAN KADAR AIR PADA WAFER LIMBAH PERTANIAN BERBASIS WORTEL - Miftahudin ,; Liman ,; Farida Fathul (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The aim of this research is to find 1) the changes of physicalquality andwater content on wafer of agricultural waste were kept in a range of different times; 2)the most effective time for savingsan wafer of agricultural waste. The research was conducted in September-November 2014 in Banjar Baru Villages, Sukau Subdistrict, West Lampung and in the Laboratory of Nutrition and Feed Livestock, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung.This research used Completely Randomized Design (CRD) with four treatments by saving the wafer for 0 week, 2 weeks, 4 weeks, and 6 weeks with fourrepetition. Data were analyzed with Analysis of Varians and continued with Least Significant Difference Test (LSD) 0,01 or 0,05.The result of this research showed that wafer with differential storage time had a signifficantly effect (P<0,01) on the water level, texture, and scent on wafer of agricultural waste. The average of water content on wafer of agricultural waste based on carrot after saved by six weeks in the amount of 42,23 %, so there was no best saving time of wafer agricultural waste based on carrot because the water content of the wafer exceeds the standard of water content of the feed material to be saved that is 14%. (Keywords: wafer, agricultural waste, water content, texture, color, scent)